No distance too far eaudiobook Home to blessing series, book 2. - Snelling, Lauraine (Home to Blessing, 2010)
CBA best-selling author Lauraine Snelling has garnered numerous awards for her novels of faith and inspiration. In No Distance Too Far, Astrid Bjorklund enrolls in a missionary training school, hoping to use her medical skills in some remote African outpost. But when she's called home to Blessing, Astrid learns of a deadly measles outbreak on a nearby Indian reservation. Feeling constrained to help, she wonders if her mission field might be much closer than she ever imagined.